Players Indifferent to Cooperate and Characterizations of the Shapley Value - Conrado Manuel; Enrique Gonzalez-Aranguena; van den Brink (Tinbergen Institute, 2012)
In this paper we provide new axiomatizations of the Shapley value for TU-games using axioms that are based on relational aspects in the interactions among players. Some of these relational aspects, in particular the economic or social interest of each player in cooperating with each other, can be found embedded in the characteristic function. We define a particular relation among the players that it is based on mutual indifference. The first new axiom expresses that the payoffs of two players who are not indifferent to each other are affected in the same way if they become enemies and do not cooperate with each other anymore. The second new axiom expresses that the payoff of a player is not affected if players to whom it is indifferent leave the game. We show that the Shapley value is characterized by these two axioms together with the well-known efficiency axiom. Further, we show that another axiomatization of the Shapley value is obtained if we replace t he second axiom and efficiency by the axiom which applies the efficiency condition to every class of indifferent players. Finally, we extend the previous results to the case of weighted Shapley values.
urn:NBN:nl:ui:31-1871/38497
Keywords: C71; 330; TU-game; Shapley value; axiomatization; indifferent players; weighted Shapley values; Transferable Utility Games; Shapley-Wert; Kooperatives Spiel; Theorie